2010
DOI: 10.15560/6.2.292
|View full text |Cite
|
Sign up to set email alerts
|

Scorpions, state of Bahia, northeastern Brazil

Abstract: The state of Bahia's main climatic characteristic is the high spatial and chronological variability of precipitation. This heterogeneity may be used to determine of pluviometrically homogeneous areas that can define mesoregions in the state, since they allow better management of water resources and help in the elaboration of agricultural studies. The mesoregions already proposed by the scientific community for the state were based only on the annual precipitation in the proximity of the pluviometric stations. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
23
0
7

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 9 publications
2
23
0
7
Order By: Relevance
“…Sixteen species have been recorded in the Atlantic Forest (Lourenço 2002b, Dias et al 2006Porto et al 2010). In this study, one-third of these species was found in Pernambuco.…”
Section: Discussionsupporting
confidence: 48%
See 3 more Smart Citations
“…Sixteen species have been recorded in the Atlantic Forest (Lourenço 2002b, Dias et al 2006Porto et al 2010). In this study, one-third of these species was found in Pernambuco.…”
Section: Discussionsupporting
confidence: 48%
“…The sedentary habit and microhabitat preference of the surface litter of this species are in agreement with Lira et al (2013) and may facilitate sampling by active search, making this species more visible and easier to capture. Tityus pusillus has also been recorded in the Atlantic Forest of Bahia (Porto et al 2010, Brazil and Porto 2011) and Paraíba (Dias et al 2006, as well as in the Caatinga (Bahia and Piauí) (Porto et al 2010, Brazil andPorto 2011). These findings indicate a wide distribution of this species in the northeast region and a high ecological plasticity, since they were recorded from different environments such as rain forest and dry forest.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…In South America, scorpions that are dangerous to humans belong to the Buthidae family, particularly those from the genus Tityus CL Koch, 1836 [2][3][4][5][6][7] . Among more than 130 scorpion species described in Brazil 8 , at least 11 harm humans, specifi cally the species Tityus serrulatus Lutz & Mello, 1922), T. bahiensis (Perty, 1833), T. stigmurus (Thorell 1876) and T. obscurus (Lourenço, 2008), which are responsible for serious envenomation or death, particularly in children 9 . Other scorpion species in this country from the Tityus genera reported to cause mild reactions include T. costatus (Karsch 1879), T. brazilae (Lourenço & Eickstedt, 1984), T. fasciolatus (Pessoa, 1935), T. metuendus (Pocock, 1897), T. neglectus (Mello-Leitão, 1932), T. mattogrossensis (Borelli, 1901), T. adrianoi Lourenço 2003) 10 and T. pussilus 11 .…”
mentioning
confidence: 99%